2005
DOI: 10.1089/jmf.2005.8.518
|View full text |Cite
|
Sign up to set email alerts
|

Elemental and Nutritional Analysis of Sea Buckthorn (Hippophae rhamnoidesssp.turkestanica) Berries of Pakistani Origin

Abstract: Sea buckthorn (Hippophae rhamnoides ssp. turkestanica) is a very important medicinal plant in northern areas of Pakistan. The fruit of sea buckthorn is rich in nutrients and medicinal compounds such as vitamins, carotene, flavonoids, essential oil, carbohydrates, organic acids, amino acids, and minerals. In order to compare various populations of sea buckthorn for chemical composition, eight populations from different areas of northern Pakistan were compared using fruit characteristics. Phytochemical analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 9 publications
3
27
1
2
Order By: Relevance
“…The results obtained were in confirmation with the previous reports by Sabir et al, 2005. 14 The GCMS analysis of both the oil samples revealed presence of palmitoleic acid (6.72%), eicosanoic acid (11.18%), and LA (39.71%) in HR. It was also found rich in ALA ( Figure S1).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The results obtained were in confirmation with the previous reports by Sabir et al, 2005. 14 The GCMS analysis of both the oil samples revealed presence of palmitoleic acid (6.72%), eicosanoic acid (11.18%), and LA (39.71%) in HR. It was also found rich in ALA ( Figure S1).…”
Section: Resultssupporting
confidence: 91%
“…12 Saso et al, 1999 demonstrated that presence of PUFA such as AA, LA and ALA etc. inhibit heat induced protein denaturation 13,14 Hence, it becomes essential to assess the level of protein denaturation in presence of SBT seed oil to understand its potential in chronic inflammatory conditions.…”
Section: Inhibition Of Protein Denaturationmentioning
confidence: 99%
“…Flavonoids, a large group of phenolic compounds (Sabir et al, 2005) with several well-documented biological activities beneficial to human health, are one of several important constituents of sea buckthorn berries (Barl et al, 2003). The significant position of flavonoids in our study was documented by high correlation coefficients (TFC-TAC, 0.8345; TFC-hydroxyl radical, 0.8930; TFC-nitric oxide, 0.9053; TFC-superoxide anion, 0.8635).…”
Section: Discussionmentioning
confidence: 55%
“…Sterols can be quantified by the colorimetric Liebermann-Burchard reaction (Wall, Kelley, 1947;Sabir et al, 2005), which is positive with stenols and negative with stanols (Brooks, 1970).…”
Section: Introductionmentioning
confidence: 99%